The Private Sector and Privatization in Social Services: Is the Washington Consensus `Dead'? - Santosh Mehrotra and Enrique Delamonica (Global Social Policy 2005; 5; 141, 2005)
One of the most significant developments in the 1990s in social policy in developing and transition countries has been the growth of privatization in health, education and water services - three basic services, which involve most of the Millennium Development Goals (MDGs). Welfare pluralism was very much a core element of the Washington Consensus. Despite the talk of the Washington Consensus being `dead for years', the international financial institutions have pushed for welfare pluralism in social services since the 1990s. This article critically scrutinizes the arguments and evidence that have been made in favour of greater private sector participation in these services. The article addresses what role the private sector could or should play in these services and is, thus, driven by practical policy concerns. For reasons of space, this article does not address the non-profit or nongovernmental organization (NGO) provision of basic social services (which, in most countries, is quite small in size).